147k views
2 votes
Given the functions:

f(x) = x2 - 9, and g(x) = x3 + 4x² + 8x – 7, find h(x) = f(x) + g(x).
h(x) = - x3 +5x2 + 8x - 16
h(x) = x3 + 3x² + 8x + 2
h(x) = x3 + 5x² + 8x – 16
h(x) = -x3 - 3x2 – 8x - 2
h(x) = -x3 + 3x2+8x+2

1 Answer

1 vote

Answer: h(x)=x³+5x²+8x-16

Explanation:

In this problem, we are given f(x) and g(x). The problem asks to find h(x)=f(x)+g(x). Since we are given f(x) and g(x), we can directly add them together.

h(x)=x²-9+x³+4x²+8x-7 [combine like terms]

h(x)=x³+5x²+8x-16

Now, we know that h(x)=x³+5x²+8x-16 after we have combined like terms.

User Nelson Reyes
by
4.4k points